Patterns of senescence in human cardiovascular fitness: VO2max in subsistence and industrialized populations. (10th September 2013) - Pisor, Anne C.; Gurven, Michael; Blackwell, Aaron D.; Kaplan, Hillard; Yetish, Gandhi
ABSTRACT Objectives This study explores whether cardiovascular fitness levels and senescent decline are similar in the Tsimane of Bolivia and Canadians, as well as other subsistence and industrialized populations. Among Tsimane, we examine whether morbidity predicts lower levels and faster decline of cardiovascular fitness, or whether their lifestyle (e.g., high physical activity) promotes high levels and slow decline. Alternatively, high activity levels and morbidity might counterbalance such that Tsimane fitness levels and decline are similar to those in industrialized populations. Methods Maximal oxygen uptake (VO2max) was estimated using a step test heart rate method for 701 participants. We compared these estimates to the Canadian Health Measures Survey and previous studies in industrialized and subsistence populations. We evaluated whether health indicators and proxies for market integration were associated with VO2max levels and rate of decline for the Tsimane. Results The Tsimane have significantly higher levels of VO2max and slower rates of decline than Canadians; initial evidence suggests differences in VO2max levels between other subsistence and industrialized populations. Low hemoglobin predicts low VO2max for Tsimane women while helminth infection predicts high VO2max for Tsimane men, though results might be specific to the VO2max scaling parameter used. No variables tested interact with age to moderate decline. Conclusions The Tsimane demonstrate higher levels of cardiovascular fitness than industrialized populations, but levels similar to other subsistence populations. The high VO2max of Tsimane is consistent with their high physical activity and few indicators of cardiovascular disease, measured in previous studies. Am. J. Hum. Biol. 25:756–769, 2013. © 2013 Wiley Periodicals, Inc.